Managing Feline Idiopathic Hypercalcemia With Chia Seeds (Salvia hispanica L.): A Case Series - Fantinati, Marco; Priymenko, Nathalie (Frontiers in Veterinary Science, 2020)
Background: We describe for the first time the use of chia seeds (Salvia hispanica L.) as a non-pharmacological solution in managing feline idiopathic hypercalcemia when dietary change alone fails. Case summary: Over a 2-year period of time, three female spayed, middle-aged, Domestic Shorthair cats were diagnosed with idiopathic hypercalcemia. Reason for consultation were lethargy and dysorexia, with a single episode of vomiting described in one cat and dysuria in another. Thorough diagnostic work-up included complete blood count, serum biochemistry, urinalysis, ionized calcium, calcemic hormones, parathyroid hormone-related protein and imaging of chest and abdomen. Based on different nutritional reasons, each cat was switched to a different high-moisture pet food as first-step in managing the disorder: a high-fiber diet, a diet formulated for chronic kidney disease management and a diet designed to prevent calcium oxalate urolithiasis. In the three cats, 6 weeks of dietary change alone did not result in normocalcemia. Before resorting to any pharmacological solution, supplementation to the diet of chia seeds (2 g/cat/day) was started. After 4 weeks from the introduction of Salvia hispanica L., all cats achieved normalization of ionized calcium concentration. Conclusion: Chia seeds (Salvia hispanica L.) supplementation could be a useful tool in managing feline idiopathic hypercalcemia.